A FEMINIZAÇÃO DO CUIDADO NO PROGRAMA BOLSA FAMÍLIA: REINVENÇÃO DAS TRADIÇÕES? - Corgozinho, Kamila Delfino Santos (2014)
The Bolsa Familia Program - PBF defines women as, preferentially, responsible for receiving the benefit and for compliance with requirements of the program. This concept seems to reinforce the common sense that sets family care as an obligation of women. In this sense, we can understand that the PBF has served as a legal device of feminization of the tasks it set. Thus, analyzing some of our care customs, we locate the notion of invention of traditions at this experience. The present study sought to analyze the process of empowerment of PBF s women beneficiaries in regard to the conditions imposed by the program, the traditions of care in the family and the difficult task of reconciling the housework with paid work. The study s field of research was the institution called Spiritist Group Peace, Love and Renewal - GEPAR located in Cafubá neighborhood in Niterói, Rio de Janeiro. The methodology used was the Oral History through structured interviews in which we could seek to approach the life histories of respondents and their relationship to the PBF in order to verify the its impact on gender relations. The survey results showed some interesting elements that suggested the recurrent absence of men in the domestic sphere and in compliance with the PBF s conditionalities; the women's perceptions centered on classic maternalism; the understanding of the use of the benefit geared towards the needs of children and the deadpan change in the gender division of household activities